2019
DOI: 10.4168/aair.2019.11.2.170
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned From GWAS of Asthma

Abstract: Asthma is a common complex disease of the airways. Genome-wide association studies (GWASs) of asthma have identified many risk alleles and loci that have been replicated in worldwide populations. Although the risk alleles identified by GWAS have small effects and explain only a small portion of prevalence, the discovery of asthma loci can provide an understanding of its genetic architecture and the molecular pathways involved in disease pathogenesis. These discoveries can translate into advances in clinical ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
97
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 92 publications
(110 reference statements)
1
97
1
1
Order By: Relevance
“…Genome-wide association studies (GWAS) have confirmed the contribution of genetic factors to risk of asthma with over 140 susceptibility loci having been identified over the last decade [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] . However, the risk alleles, most of which are common in the population, still only explain a small fraction of the overall heritability for asthma 25,26 . This observation implies either the existence of additional variants with smaller effect sizes, rare susceptibility alleles, and/or interactions between genes and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have confirmed the contribution of genetic factors to risk of asthma with over 140 susceptibility loci having been identified over the last decade [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24] . However, the risk alleles, most of which are common in the population, still only explain a small fraction of the overall heritability for asthma 25,26 . This observation implies either the existence of additional variants with smaller effect sizes, rare susceptibility alleles, and/or interactions between genes and environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with this notion, estimates for the heritability of asthma have ranged between 35% and 95% 3 , although those based on twin studies have been lower 4 . Genome-wide association studies (GWAS) have confirmed the contribution of genetic factors to risk of asthma, with over 140 susceptibility loci having been identified thus far [5][6][7][8][9][10][11][12][13] . However, the risk alleles, most of which are common in the population, still only explain a small fraction of the overall heritability for asthma [5][6][7] .…”
mentioning
confidence: 99%
“…Genome-wide association studies (GWAS) have confirmed the contribution of genetic factors to risk of asthma, with over 140 susceptibility loci having been identified thus far [5][6][7][8][9][10][11][12][13] . However, the risk alleles, most of which are common in the population, still only explain a small fraction of the overall heritability for asthma [5][6][7] . This observation could be due to the use of a qualitative outcome in most genetic studies, which does not depict the spectrum of asthma heterogeneity, or the existence of additional variants with smaller effect sizes, rare susceptibility alleles, and/or interactions between genes and environmental factors.…”
mentioning
confidence: 99%
“…Besides this prominent locus, SNPs in 1q31-32 (IL-10), 2q12 (IL-1RL1/IL-18R1), 5q22 (thymic stromal lymphopoietin (TSLP)), 5q31.1 (interferon regulatory factor 1 (IRF1)), 6q21 (human leukocyte antigens (HLA)-DR), and 9p24 (IL-33) have been identified as asthma susceptibility loci [49]. Their immunological role involves primarily the regulation of Th1/Th2 immunity (IL10, IL-1RL1, IL-18R1, TSLP, IL33, IRF1) and antigen presentation (HLA-DR).…”
Section: Role Of Geneticsmentioning
confidence: 99%